2015
DOI: 10.1007/s00360-015-0951-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA regulation in heart and skeletal muscle over the freeze–thaw cycle in the freeze tolerant wood frog

Abstract: The North American wood frog, Rana sylvatica, is one of just a few anuran species that tolerates whole body freezing during the winter and has been intensely studied to identify the biochemical adaptations that support freeze tolerance. Among these adaptations is the altered expression of many genes, making freeze-responsive changes to gene regulatory mechanisms a topic of interest. The present study focuses on the potential involvement of microRNAs as one such regulatory mechanism and aims to better understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…Furthermore, aldose reductase levels increased during rehydration, possibly as a result of restored blood volume and flow to the liver, as well as a need to metabolize excess glucose in the liver. The fact that we see such discrepancies between NFAT5 levels and the protein levels of BGT-1 and SMIT stress the possibility that mRNA processing through miRs and stress granules play a vital role in regulating protein translation and mRNA stability in a tissue- and stress-dependent manner, and these mechanisms are only just being discovered in frogs (Wilczynska et al, 2005; Bansal, Luu & Storey, 2016). …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, aldose reductase levels increased during rehydration, possibly as a result of restored blood volume and flow to the liver, as well as a need to metabolize excess glucose in the liver. The fact that we see such discrepancies between NFAT5 levels and the protein levels of BGT-1 and SMIT stress the possibility that mRNA processing through miRs and stress granules play a vital role in regulating protein translation and mRNA stability in a tissue- and stress-dependent manner, and these mechanisms are only just being discovered in frogs (Wilczynska et al, 2005; Bansal, Luu & Storey, 2016). …”
Section: Discussionmentioning
confidence: 74%
“…This delayed response in SMIT upregulation may come as a result of post-transcriptional modifications, such as inhibition by microRNAs (miR). In fact, several miRs have been shown to be differentially regulated during freezing in R. sylvatica (Bansal, Luu & Storey, 2016). Aldose reductase displayed a different pattern of protein expression in comparison with the other targets, where its protein levels were significantly decreased by 37% and 41% during anoxia and recovery, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these would have actions that are advantageous for freezing survival, as discussed above. Overall, then, the miRNA actions in response to freeze/thaw were generally consistent with protecting and stabilizing cells and suppressing energy‐expensive processes in the frozen state with a reversal after thawing that would rapidly assist repair and recovery of cells …”
Section: Microrna and Mitochondriamentioning
confidence: 79%
“…In skeletal muscle 16 miRNA species showed increased expression during freezing (indicating suppression/storage of mRNA transcripts under their control) whereas 21 showed reduced abundance in heart after thawing (implying enhanced transcription of mRNA transcripts that they controlled). 35 Evaluation of the putative mRNA targets of 12 differentially expressed miRNAs in skeletal muscle using DIANA miRPath target enrichment analysis indicated that these target many genes mapped with the actin cytoskeleton and with signaling pathways involving PI3K (phosphoinositide 3-kinase), Akt (also known as protein kinase B) and MAPKs (mitogen-activated protein kinases). Freezing causes a major reduction in cell volume that is bound to disrupt the actin cytoskeleton but attempts to repair this in the frozen state could be largely futile (and highly energyexpensive).…”
Section: Microrna and Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation